The use of portfolios to develop first year students’ writing skill at Foreign Trade University = \b Việc sử dụng hồ sơ tập bài để phát triển kĩ năng viết của sinh viên năm thứ nhất tại trường đại học Ngoại thương. M.A. Thesis Linguistics: 60 14 01 11 - Đỗ, Thị An (University of Languages and International Studies, 2017)
This study was carried out for two aims –first, tofind out the roles of portfolio in teaching and learning EFL writing and its theoretical bases; second, to evaluate the effectiveness of portfolio on developing EFL students’ writing skilland increasing their motivation.To fulfill the objectives, quasi experimental research was utilized. 40 first-year students were chosento take part in the experiment –a writing course. They also answered questionnaire and completedself assessment. The collected data then were cautiously analyzed.The resultsof this research are, in summary, quite positive. Using portfolio, as a complementary to traditional tests, in teaching and assessing EFL writing was recommended and that assessment should be an integral part of the teaching process. The study concluded that writing portfolio is found to be an effective instructional strategy to improve students’ writing skill and enhances theirEnglish writing motivation. In addition, portfolio assessment strategy allows students to create a bridge between their teacher and themselves when students get feedback from their peer and teacher. Based on the findings of the study, one extremely important recommendation is that portfolio should be planned and implemented by EFL teachers in writing classes at Foreign Trade University. Though the limitations have been unavoidable, the study is expected to be beneficial to teachers, students and researchers of the related studies